Perubahan Kebijakan Subsidi Pupuk dan Dampaknya Terhadap Penerapan Teknologi dan Pendapatan Usahatani Padi di Kabupaten Cianjur - Pandanwangi, Nurfadilah Ros; Dasipah, Euis; Mulyana, Tatang (Papanda Publisher, 2024)
This research uses the verification method to examine the impact of fertilizer subsidy policy changes on wetland rice farmers in Gekbrong Sub-district, Cianjur District. This method was chosen to evaluate how far the objectives of the new fertilizer subsidy policy (October 2022) achieved the expected results. Data analysis was conducted using paired t-test and Wilcoxon Signed Rank Test, depending on the data distribution. The research sample consisted of 42 farmers who had been farming before and after the implementation of the new policy. The results showed that there was no significant difference in the application of fertilizer technology between before and after the policy change, although the new policy aimed to encourage the use of organic fertilizer. However, the change in fertilizer subsidy policy had a significant impact on farmers' income due to an increase in farming costs, particularly fertilizer procurement costs. This finding suggests that the subsidy distribution mechanism still suffers from “irregularities” and requires improvement to ensure farmer income sustainability.